Bioalgorithms for Optical Networks: New Heuristic Based on Hyphae [Bioalgoritmos Para Redes Ópticas: Nueva Heurística Basada en Hifas] - Ganga-Munoz, M; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Universidad de Tarapaca, 2021)
Optical networks have been positioned as high-speed networks whose switches must respond to requests at rates that did not occur before, determining that static traffic evolving into dynamic traffic caused the routing problem, and the wavelength assignment cannot be solved with optimization processes, giving rise to the appearance of heuristic algorithms which, because they are iterative processes, do not seek to optimize and find absolute optimums. It is only necessary to find a suitable solution, and in the case of networks this means a good route without it being the optimal route. Different strategies and algorithms have been used with outstanding results, and recently bioalgorithms have appeared that allow finding solutions from a biological perspective such as genetic and bacterial algorithms. In the present investigation, an algorithm based on fungal hyphae is proposed. The comparison of similar heuristics was performed through numerical simulation, where improvements were obtained with the proposed heuristic for the indicators under study. The results are encouraging and develop a performance that stands out among bioalgorithms. © 2021, Universidad de Tarapaca. All rights reserved.